2010
DOI: 10.1002/adma.201002131
|View full text |Cite
|
Sign up to set email alerts
|

Yarn‐Like Carbon Nanotube Fibers

Abstract: A fiber made of carbon nanotubes is shown to resemble a conventional yarn in terms of its structure, composed of discrete fibrillar sub‐units, and its properties, such as high flexibility in bending, cutting resistance and 100% knot efficiency. Its combination of yarn‐like character and tensile properties in the high‐performance range make this CNT fiber an exceptional new material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(135 citation statements)
references
References 17 publications
3
132
0
Order By: Relevance
“…Moreover, unlike the conventional carbon fibres, CNT fibres can be bent through very tight radii without apparent permanent damage, and can show excellent knot efficiency, as has been shown previously [4]. It means that in handling, there are no surface damage issues, and, moreover, it reveals the radically different fracture mechanism, discussed in the following section, suggests that the composites should be much more resistant to the propagation of transverse cracks or defects.…”
Section: Discussion Two Areas Of Comparisonmentioning
confidence: 73%
See 3 more Smart Citations
“…Moreover, unlike the conventional carbon fibres, CNT fibres can be bent through very tight radii without apparent permanent damage, and can show excellent knot efficiency, as has been shown previously [4]. It means that in handling, there are no surface damage issues, and, moreover, it reveals the radically different fracture mechanism, discussed in the following section, suggests that the composites should be much more resistant to the propagation of transverse cracks or defects.…”
Section: Discussion Two Areas Of Comparisonmentioning
confidence: 73%
“…They are highly elongated and interconnected with the result that the resin penetrates the condensed fibres and fills the voids [12,13]. The interconnected voids are also confirmed by the specific surface area of the fibre which can be up to 200 m 2 /g depending on the synthesis conditions [4,13,14]. The oriented CNT mat comprises a far less dense network of laterally entangled aligned nanotube bundles (Fig.…”
Section: Carbon Nanotube Assembliesmentioning
confidence: 79%
See 2 more Smart Citations
“…[189] S-/DWCNT growth needs not only good dispersion of the active metal components on the catalyst support and a suitably large BET surface area, but also a proper catalyst structure. Any factor that can enlarge the pore size or reduce the strength of the catalyst (including the direct formation of large pores in a catalyst by a template, controlled critical drying of the catalyst, [85] minimizing catalyst support size, [190,191] aerosol catalyst, [67,192,193] or direct spray drying of the catalyst into very fine powders [194] ) can provide a catalyst with a low bulk density and weak interaction in the agglomerates that will meet the requirements for ). [189] Recently, Nie et al reported that an ethanol-thermal treatment was effective for increasing the percentage of very large pores in the porous catalyst structure, and can be used for the growth of very high quality SWCNTs with much fewer defects.…”
Section: Formation Of Cnt Agglomeratesmentioning
confidence: 99%